Contraceptive use among women who desire no more children in Indonesia: a cross-sectional study of a national survey - Maria Gayatri; Desy Nuri Fajarningtiyas (Malaysian Family Physician)
Introduction: The desire for no additional births may be used to estimate the demand for family planning. Couple education may influence contraceptive use. This study aimed to examine the relationship between education and contraceptive use among women who desire no more children in Indonesia. Methods: A dataset from the 2017 Indonesia Demographic and Health Survey (IDHS) was used. The sample consisted of 17,938 women aged 15–49 years who desired no more children. Binary logistic regression was conducted for data analyses. Results: Of the total respondents, 73% used contraceptive methods. Contraceptive use was strongly associated with secondary education among couples (odds ratio [OR]=1.27; 95% confidence interval [CI]=1.17–1.37) and the working status of the husband (OR=2.62; 95% CI=2.07–3.32). The respondents living in rural areas (OR=1.14; 95% CI=1.06–1.23) and in the Java-Bali region (OR=1.36; 95% CI=1.27–1.46) were more likely to use contraceptive methods. However, the respondents aged more than 35 years were less likely to use contraceptives. Conclusion: Among women who desire no more children, contraceptive use is associated with educational level, age and place of residence. Educated women tend to be empowered and have better access to contraceptive services, improving their chances of using contraception. Healthcare providers and policymakers need to promote the use of contraceptive services including counselling for couples with a low educational level, urban women and women who live in the outer Java-Bali region.